개념미술을 계승한 버질 아블로의 타이포그래피 표현과 의의 - 이재원; Lee Chae (기초조형학연구, 2023)
타이포그래피가 미술의 문맥에서 차용된 이후로 현재에 이르기까지 미술과 그래픽디자인 분야를 넘어 패션디자인까지 그 범위를 확장하고 있으며, 이것을 이해하기 위해서는 그 시기 타이포그래피의 표현차용 사례들을 이론적으로 살펴보는 것이 중요하다. 이는 타이포그래피가 다양한 영역의 형식과 매체를 매개하는 실험적인 표현 방식임을 기록하고 관련 연구를 발전시키기 위해 필요하다. 본 연구의 목적은 개념미술에서 개념적 언어/텍스트의 표현 양식으로 활용된 타이포그래피가 미술을 넘어 그래픽 디자인과 패션 디자인으로 확장해 개념미술을 계승하고 있다는 가능성을 전제로, 개념적 언어/텍스트의 표현을 전유하는 후행 과정과 현대미술의 맥락 내에서 수용되고 있는 사례들을 통해 분석하고, 이를 패션 디자인에서의, 특히 버질 아블로 타이포그래피의 유사성과 연결 짓는 것이 목적이다. 연구방법은 개념적 언어/텍스트의 표현 양식으로서의 타이포그래피와 출판의 궤적을 추적하고 분석하여 ‘전시로서의 출판’에서 ‘전시로서의 패션’으로 이어지는 개념미술을 이론적으로 고찰하고자 하였다. 그리고 개념미술의 표현 특징인 언어와 레디메이드를 분석의 틀로 한 타이포그래피가 출판 그리고 전시에 적용되어, 어떻게 진화하고, 또 소비재로서 어떻게 유통되고 있는지를 연구하고자 했다. 최근에는, 개념적 타이포그래피와 출판의 쓰임이 미술과 시각 디자인의 영역을 넘어 패션디자인까지 그 범위를 넓히고 있고, 영역을 매개하고 확장하는 소비재의 역할로서 다양한 매체를 유기적으로 활용하고 있다. 이런 경향은 타이포그래피의 역할 및 위상을 방증하는 것으로 해석할 수 있었다. 본 연구를 통해 타이포그래피가 효과적인 시각 매개제로서 개념미술을 계승함과 동시에 다변화하고 있음을 고찰할 수 있었고, 타이포그래피가 현재와 미래에서 다양한 영역을 매개하는 탈중앙화된 협업의 도구로서 변용과 변주의 무한한 가능성을 가진 흥미로운 표현 방식임을 확인할 수 있었다. Since typography’s appropriation in the context of conceptual art, it has expanded beyond the fields of art and graphic design to extend its reach into fashion design, and to understand this, it is important to theorize about the expressive appropriations of typography during this period. This is needed to document typography as an experimental mode of expression that mediates between forms and media in a variety of domains, and to advance related research. The purpose of this study is to analyze the possibility that typography, which has been utilized as a form of expression of conceptual language/text in conceptual art, is inheriting conceptual art by expanding beyond art to graphic design and fashion design, and to connect it with the similarity of fashion designer Virgil Abloh’s typography through a trailing process of appropriation and acceptance within the context of contemporary art. The research method was to trace and analyze the trajectory of typography and publishing as a form of expression of conceptual language/text to theoretically consider conceptual art from ‘publishing as exhibition’ to ‘fashion as exhibition.’ In addition, I wanted to study how typography, which is characterized by language and ready-made as the expressive features of conceptual art, is applied to publication and exhibition, evolves, and how it is distributed as a consumer product. In recent years, the use of conceptual typography and publishing has expanded beyond the realm of art and visual design to include fashion design, organically utilizing various media as a consumer product that mediates and expands its scope. This trend can be interpreted as a demonstration of the role and status of typography. Through this study, we were able to consider that typography is inheriting and diversifying conceptual art as an effective visual medium, and that typography is an interesting mode of expression with infinite possibilities of transformation and variation as a tool for decentralized collaboration that mediates various fields in the present and future.